2013
DOI: 10.1007/s00347-013-2815-0
|View full text |Cite
|
Sign up to set email alerts
|

Augenmanifestationen bei Churg-Strauss-Syndrom

Abstract: This paper summarizes the possible ocular manifestations of Churg-Straus syndrome (CCS) from the literature and presents an unusual case report from routine clinical practice with conjunctival granuloma, orbital pseudotumor and choroidal folds. The CSS is an ANCA-associated granulomatous vasculitis which can be manifested in various organs and represents a life-threatening situation for the patient. Ocular manifestations are rare and can spread to all segments of the eye and orbit. The most frequent forms of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The early phase of Churg-Strauss syndrome is characterized by extravascular eosinophilic tissue infiltration in virtually any organ. However, breast involvement is extremely rare [ 31 , 39 ]. It has been previously reported that masses and mastitis are manifestations of breast compromise [ 38 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The early phase of Churg-Strauss syndrome is characterized by extravascular eosinophilic tissue infiltration in virtually any organ. However, breast involvement is extremely rare [ 31 , 39 ]. It has been previously reported that masses and mastitis are manifestations of breast compromise [ 38 , 40 ].…”
Section: Discussionmentioning
confidence: 99%